Cleaner - Renny Harlin; Ed, Harris; Samuel L Jackson; Marc Macaulay; Robert Forster; Luis Guzman (Sony Pictures USA, 2007)
Single father and former cop Tom Carver (Samuel L. Jackson) has an unusual vocation - he cleans up crime scenes. But when he's called in to sterilize a wealthy suburban residence after a brutal shooting, Carver is shocked to learn he may have unknowingly erased crucial evidence, entangling himself in a dirty criminal cover up. Directed by Renny Harlin and co-starring Eva Mendes, Ed Harris, Keke Palmer, and Luis Gusman, Cleaner is a dark, gritty crime thriller that proves cleaning up is the dirtiest job there is.
Language(s): English Subtitle(s): English
Keywords: Action; Adventure